2012
DOI: 10.1128/jvi.00380-12
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Uncoupled Histone Deposition during Adenovirus DNA Replication

Abstract: In infected cells, the chromatin structure of the adenovirus genome DNA plays critical roles in its genome functions. Previously, we reported that in early phases of infection, incoming viral DNA is associated with both viral core protein VII and cellular histones. Here we show that in late phases of infection, newly synthesized viral DNA is also associated with histones. We also found that the knockdown of CAF-1, a histone chaperone that functions in the replication-coupled deposition of histones, does not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 52 publications
8
50
0
Order By: Relevance
“…Next we sought to examine the underlying mechanisms of how PML-NB components recruit and/or are recruited into DBP structures. In the previous study, we showed that deletion of the C-terminal extension of DBP, which is necessary for its oligomerization (31), results in loss of the formation of the subnuclear structures in cells (35). Consistent with the previous observation, the deletion mutant of DBP (DBP⌬C) localized only diffusely in the nucleus, independently of its expression levels, and did not show any specific association with PML-NBs (Fig.…”
Section: Dbp Targets Pml-nbs and Recruits Its Components In The Absensupporting
confidence: 76%
See 2 more Smart Citations
“…Next we sought to examine the underlying mechanisms of how PML-NB components recruit and/or are recruited into DBP structures. In the previous study, we showed that deletion of the C-terminal extension of DBP, which is necessary for its oligomerization (31), results in loss of the formation of the subnuclear structures in cells (35). Consistent with the previous observation, the deletion mutant of DBP (DBP⌬C) localized only diffusely in the nucleus, independently of its expression levels, and did not show any specific association with PML-NBs (Fig.…”
Section: Dbp Targets Pml-nbs and Recruits Its Components In The Absensupporting
confidence: 76%
“…Since no colocalization between incoming Ad genome complexes and PML-NBs was observed, we speculated that PML-NBs and/or its components might recruit or be recruited to viral DNA replication components/compartments independently of viral genomes. Previously we reported that transiently expressed DBP forms subnuclear structures through its oligomerization in the absence of any other viral components and proposed that by forming these structures, DBP establishes an environment conducive for viral DNA replication (35). Here we hypothesized that DBP itself may also have the ability to associate with and/or modulate PML-NBs and/or its components.…”
Section: Dbp Targets Pml-nbs and Recruits Its Components In The Absenmentioning
confidence: 99%
See 1 more Smart Citation
“…During herpesvirus lytic infection, the viral genomes are associated with histones immediately after injection into the nucleus, and viral proteins are required to enhance histone acetylation to allow for efficient viral gene expression (40)(41)(42)(43)(44). Moreover, studies of infection by an adenovirus have shown that viral proteins mediate the transcriptional activation of viral promoter regions (45)(46)(47). In this work, we first observed that the progress of CPV infection was accompanied by the enrichment of H3 histones in the enlarged APAR body area.…”
Section: Discussionmentioning
confidence: 62%
“…Since this discovery, the importance of the chromatinization of the viral genome in DNA damage (30) and transcription control (31,32) has become increasingly apparent. Previous work from our lab has further shown regulatory roles for chromatin modifications within the promoter regions of the viral genome (6).…”
Section: Discussionmentioning
confidence: 99%